f(x) = 7x^2+3
g(x) = 2x-9
g(f(x)) = 2(7x^2+3) - 9
g(f(x)) = 14x^2 -3
g(f(2)) = 14(2)^2 -3
g(f(2)) = 56-3 = 53
2007-01-10 03:04:25
·
answer #1
·
answered by seah 7
·
2⤊
0⤋
Strict substitution.
f(2) means to take f(x) and put in a 2 everywhere that the formula has an x. Thus:
f(2) = 7(2)^2 + 3 = 7(4)+3 = 28 + 3 = 31
g(f(2)) means to take g(x) and put in the result of f(2) everywhere that the formula has an x. Thus:
g(f(2)) = 2(31) - 9 = 62 - 9 = 53
2007-01-10 11:02:20
·
answer #2
·
answered by TimmyD 3
·
1⤊
0⤋
Remember in the order of operations, paretheses always come first.
First figure f(2) which equals 7*2² + 3 = 7*4 + 3 = 28 + 3 = 31
Now figure g(31) = 2*31 - 9 = 62 - 9 = 53. QED
2007-01-10 11:00:43
·
answer #3
·
answered by Dave 6
·
0⤊
0⤋
First, f(2)=7*2^2+3= 31.
And g(31)=2*31-9=62-9=53.
2007-01-10 11:01:22
·
answer #4
·
answered by yljacktt 5
·
0⤊
0⤋
first you calculate f(2) by replacing x with 2;if f(x)=7(x*x)+3 that means that f(2)=7(2*2)+3=7*4+3=31
then you replace x from g(x) with f(2).if g(x)=2x-9 you get g(f(2))=2*31-9=62-9=53.
Easy as that.
2007-01-10 11:10:14
·
answer #5
·
answered by teo 1
·
0⤊
0⤋
g(f(2)) means that replace the "x" in g(x) by the function f(2)
I'll show you
First solve f(2) = 7 * 2^2 + 3 = 31
g(f(2)) = 2 (31) - 9 = 53
2007-01-10 11:10:07
·
answer #6
·
answered by Anonymous
·
1⤊
0⤋
You evaluate f(x) and then put the answer into g(x).
Solution:
f(x) = 7x^2 + 3
f(2) = 7(2^2) + 3
f(2) = 7(4) +3
f(2) = 28 + 3
f(2) = 31.
g(x) = 2x - 9
g(31) = 2(31) - 9
g(31) = 62 - 9
g(31) = 53.
Q.E.D
2007-01-10 11:05:36
·
answer #7
·
answered by Mark O'L 1
·
0⤊
0⤋
f(2)=7*4+3
f(2)=31
g(31)=2*31-9
=62-9
=53
2007-01-10 11:04:00
·
answer #8
·
answered by miinii 3
·
0⤊
0⤋